Preserving Tradition: Cultural Immersion in English Educational Context of University of Western Australia Students in Toraja - Girik Allo, Markus Deli; Baka, Charlie; la’biran, Roni; Pongsapan, Nehru P.; Sampelolo, Rigel; Palimbong, Daud Rodi; Ury, Ury (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The objective of this study is to examine the impact of this immersion on both the students and the local community, focusing on the preservation of Toraja cultural traditions.This study adopts a qualitative research design which is particularly suited for exploring the depth and complexity of participants' experiences and perspectives. The participants in this study include students from the University of Western Australia (UWA), faculty members from Universitas Kristen Indonesia Toraja (UKI Toraja), and members of the Toraja community. Participant Observation: Researchers closely observed the participants' daily interactions, behaviors, and activities during the immersion program. Detailed field notes were maintained to document the observations. Focus Group Discussions (FGDs): Semi-structured focus group discussions were conducted with the UWA students to explore their learning outcomes, reflections, and overall experiences of the cultural immersion program. Participants were selected using purposive sampling, a non-probability sampling technique where participants are chosen based on specific characteristics and their relevance to the research questions. UWA students were selected based on their active participation in the Bali Studio Program, while UKI Toraja faculty members and Toraja community members were chosen for their roles in facilitating and engaging with the cultural immersion activities. The data collected from participant observations and focus group discussions were analyzed using thematic analysis. The result of this study shows that the positive impact of this immersion on both the students and the local community, focusing on the preservation of Toraja cultural traditions. The evidence depicted that the deep and impactful engagement of UWA students with Toraja culture and the presence of UWA students in the Toraja community had a positive impact on cultural preservation efforts. The study concludes with recommendations for improving the effectiveness of such programs and calls for continued collaboration between universities and indigenous communities in the pursuit of cultural preservation.